The effect of therapeutic massage combined with conventional therapy in children with functional dyspepsia: a systematic review and meta-analysis - Lin, Shaohong; Ye, Ruming; Wu, Guanhong; Wu, Lixia; Lin, Ying; Li, Dan; Xie, Namei; Zhang, Huiyue (Frontiers in Pharmacology, 2025)
BackgroundTherapeutic massage has been widely used for functional dyspepsia (FD) in children. Emerging evidence suggests that it serves as an effective complementary therapy for pediatric FD. However, no related systematic reviews have been published to date.ObjectiveTo conduct a systematic review and meta-analysis to evaluate the effectiveness of therapeutic massage in conjunction with conventional therapy for children with FD.MethodsA search was conducted across PubMed, the Cochrane Library, and nine additional databases, up to November 2024. We included randomized controlled trials (RCTs) that recruited children with functional dyspepsia. These trials compared therapeutic massage combined with conventional therapy to conventional therapy alone. Dichotomous symptom data were aggregated to calculate the relative risk (RR) of overall response following therapy. Continuous data were aggregated utilizing a standardized mean difference with a 95% confidence interval.ResultsThe search identified 1,190 citations. Twelve RCTs were eligible for inclusion, which contained 1,161 patients. The response rate of combination therapy, which includes therapeutic massage alongside conventional therapy, was found to be superior to that of conventional therapy alone. Subgroup analysis indicated that both point massage and chiropractic, when combined with conventional therapy, also demonstrated superior response rates compared to conventional therapy alone. Subgroup analysis of the frequency of intervention over a 2-week duration of therapeutic massage indicated that the overall response rates for combination therapy at frequencies of five times per week and seven times per week were superior to those of conventional therapy. In comparison to conventional therapy, combination therapy markedly reduced symptom scores related to abdominal pain, flatulence, anorexia, eructation, nausea and vomiting, and early satiety. Additionally, it enhanced levels of growth hormone-releasing peptide, neuropeptide Y, motilin, and gastrin, while decreasing levels of 5-hydroxytryptophan.ConclusionResults demonstrated that compared to conventional therapy, therapeutic massage combined with conventional therapy can significantly reduce symptoms and enhance gastrointestinal hormone levels in children with functional dyspepsia. However, due to the heterogeneity of the findings and the low quality of evidence, further extensive and methodologically sound trials are necessary to validate whether therapeutic massage can serve as an effective complementary therapy for pediatric functional dyspepsia.Systematic Review Registration:identifier CRD42024540844.